Life-History Parameters of Phyllotreta striolata (F.) (Coleoptera: Chrysomelidae) Acquired by a Laboratory-Rearing Method - Yiyun Wei; Jincheng Zhou; Bin Chen; Panpan Tian; Chen Luo (Insects)
Phyllotreta striolata (Fabricius) (Coleoptera: Chrysomelidae) is one of the most damaging pests affecting vegetables. This pest feeds on the leaves and roots of Brassicaceae plants during their adult and larval stages, respectively, resulting in substantial economic losses. The laboratory-rearing methods for P. striolata and its life-history parameters have not been fully studied. This study developed a laboratory method for the generational rearing of P. striolata, including techniques for egg collection and rearing immature individuals, which allows for the continuous observation and collection of individuals at various developmental stages. This method established five F1 populations and three consecutive generations of P. striolata from various field-collected parent populations. During the rearing process, developmental durations and survival rates at four stages of P. striolata were acquired, confirming the method’s effectiveness. The female ratio, tibia length of the hind leg, and fluctuating asymmetry of adults in three of the five F1 populations were measured to assess P. striolata’s adaptability to the rearing conditions. The established laboratory-rearing method and life-history parameters of P. striolata could potentially contribute to research in its ecology, population dynamics prediction, and pest management.